How the Mediation Effect of Job Stress on the Relationship between Safety Leadership, Safety Culture and Safety Performance - Supardi, Supardi; Sudiantini, Dian (Dinasti Publisher, 2024)
Indonesia's mining company's safety performance in the last 2 years has seen a downward trend. The study aims to investigate the mediation effects of job stress on relationships between safety leadership, safety culture and safety performance. The research data is a questionnaire from the production department of coal mining companies in the Eastern Kalimantan Provinces. Sampling method are taken using the proportionate random sampling, with the number of respondents as many as 161 workes. The method of data analysis using of structural equation modelling. The findings of this study suggest that leadership, culture and job stress are having a positive effect on safety performance. The direct influence of safety leadership and the safety culture on safety performance is stronger than through the job stress. The direct influence of safety leadership on the safety performance is more powerful than the influence of the safety culture on the safety performance.